Modern water/rock reactions in Oman hyperalkaline peridotite aquifers and implications for microbial habitability. (15th April 2016) - Miller, Hannah M.; Matter, Jürg M.; Kelemen, Peter; Ellison, Eric T.; Conrad, Mark E.; Fierer, Noah; Ruchala, Tyler; Tominaga, Masako; Templeton, Alexis S.
Abstract: The Samail ophiolite in Oman is undergoing modern hydration and carbonation of peridotite and may host a deep subsurface biosphere. Previous investigations of hyperalkaline fluids in Oman have focused on fluids released at surface seeps, which quickly lose their reducing character and precipitate carbonates upon contact with the O2 /CO2 -rich atmosphere. In this work, geochemical analysis of rocks and fluids from the subsurface provides new insights into the operative reactions in serpentinizing aquifers. Serpentinite rock and hyperalkaline fluids (pH > 10), which exhibit millimolar concentrations of Ca 2+, H2 and CH4, as well as variable sulfate and nitrate, were accessed from wells situated in mantle peridotite near Ibra and studied to investigate their aqueous geochemistry, gas concentrations, isotopic signatures, mineralogy, Fe speciation and microbial community composition. The bulk mineralogy of drill cuttings is dominated by olivine, pyroxene, brucite, serpentine and magnetite. At depth, Fe-bearing brucite is commonly intermixed with serpentine, whereas near the surface, olivine and brucite are lost and increased magnetite and serpentine is detected. Micro-Raman spectroscopy reveals at least two distinct generations of serpentine present in drill cuttings recovered from several depths from two wells. Fe K-edge X-ray absorption near-edge spectroscopy (XANES) analysis of the lizardite shows a strong tetrahedral Fe coordination, suggesting a mixture of both Fe(II) and Fe(III) in the serpentine. Magnetite veins are also closely associated with this second generation serpentine, and 2–10 μm magnetite grains overprint all minerals in the drill cuttings. Thus we propose that the dissolved H2 that accumulates in the subsurface hyperalkaline fluids was evolved through low temperature oxidation and hydration of relict olivine, as well as destabilization of pre-existing brucite present in the partially serpentinized dunites and harzburgites. In particular, we hypothesize that Fe-bearing brucite is currently reacting with dissolved silica in the aquifer fluids to generate late-stage magnetite, additional serpentine and dissolved H2 . Dissolved CH4 in the fluids exhibits the most isotopically heavy carbon in CH4 reported in the literature thus far. The CH4 may have formed through abiotic reduction of dissolved CO2 or through biogenic pathways under extreme carbon limitation. The methane isotopic composition may have also been modified by significant methane oxidation. 16S rRNA sequencing of DNA recovered from filtered hyperalkaline well fluids reveals an abundance of Meiothermus, Thermodesulfovibrionaceae (sulfate-reducers) and Clostridia (fermenters). The fluids also contain candidate phyla OP1 and OD1, as well as Methanobacterium (methanogen) and Methylococcus sp. (methanotroph). The composition of these microbial communities suggests that low-temperature hydrogen and methane generation, coupled with the presence of electron acceptors such as nitrate and sulfate, sustains subsurface microbial life within the Oman ophiolite.